Penerapan Community Based Tourism Dalam Pengelolaan Daya Tarik Wisata Pantai Lon Malang Kabupaten Sampang - Tri Utami Aprilia; Alifah Rokhmah Idialis (JURNAL DESTINASI PARIWISATA, 2022)
Community Based Tourism is a tourism concept that makes the community the subject of tourismdevelopment. Lon Malang Beach is one of the priority tourist destinations in Sampang Regency that appliesthis community-based tourism concept. This research aims to see how the application of the principles ofCommunity Based Tourism in Lon Beach Malang and see how the role of stakeholders involved in tourismdevelopment. This research uses a qualitative descriptive approach with data collection methods in the formof observation, interviews, and documentation. The subjects in this study using purposive samplingtechniques. The results of this study show that the development of Lon Malang beach tourism has applied theprinciple of Community Based Tourism, where full tourism management is carried out by local communitiesthrough village institutions such as POKDARWIS and BUMDes. The results of the study also show thatstakeholders have played a role in the development of Lon Malang beach tourism and cooperate with eachother.Keywords: Community Based Tourism, Tourism, Community Participation, Stakeholders